Magneto‐Sensitive Elastomers: An Experimental Point of View. Issue 1 (December 2014) - Walter, Bastian; Saxena, Prashant; Kaschta, Joachim; Schubert, Dirk W.; Steinmann, Paul
Abstract Magneto‐sensitive elastomers (MSEs) are smart materials changing their shape and mechanical properties in the presence of a magnetic field. Focussing on model systems, silicone based MSEs are prepared by a multi‐step mixing process and characterised using a rotational rheometer (plate‐plate). Data obtained by relaxation tests is used to set‐up a material model coupling the theories of viscoelasticity and magnetoelasticity. The behaviour of MSEs in quasi‐static and dynamic mechanical shear experiments can be successfully predicted by the analytical model using parameters received by fitting the transient experiments. The model is validated for small shear deformations (γ = 0.02) and low magnetic fields (𝔹 = 0.2 T). (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)